Pengaruh model pembelajaran kooperatif tipe team games tournament (TGT) terhadap kemampuan komunikasi matematis kelas VIII SMPN Masbagik Tahun Ajaran 2024/2025 - Hijriati, Awwalus sanatil; Arjudin; Wulandari, Nourma Pramestie; Baidowi (Mandalika Mathematics and Educations Journal, 2025)
This study aims to determine the effect of the Team Game Tournament (TGT) type cooperative learning model on the mathematical communication skills of 8th-grade students at SMPN 6 Masbagik. The research employed a quantitative approach using a true experimental method with a posttest only control group design. The population consisted of all 8th-grade students at SMPN 6 Masbagik in the 2024/2025 academic year, totaling 76 students. The sample was selected using a cluster random sampling technique, with two classes selected from three, namely classes VIIIA and VIIIB, each consisting of 26 students. The two classes received different treatments: class VIIIA as the experimental class using the TGT learning model, and class VIIIB as the control class using conventional learning. Data were collected through a mathematical communication skills test and observation. Data analysis included normality and homogeneity tests, hypothesis testing using the Independent Sample t-Test, and an effect size test. The results showed that the average posttest score in the experimental class was 69.5, while the control class scored 55. The t-test result showed a t-count of 4.434 > t-table 2.008, indicating a significant difference. The effect size result of 1.09 falls into the large category. In conclusion, the TGT model significantly affects students' mathematical communication skills.